2012
DOI: 10.1002/ajh.23170
|View full text |Cite
|
Sign up to set email alerts
|

A shorter time to the first treatment may be predicted by the absolute number of regulatory T‐cells in patients with Rai stage 0 chronic lymphocytic leukemia

Abstract: Regulatory T-cells (Tregs) are increased in chronic lymphocytic leukemia(CLL) and correlates with clinical and biological features of active/progressive disease. However, little is known about their ability to predict the time to first treatment (TFT). We evaluated 75 patients with Rai stage 0 CLL, in whom the absolute number of Tregs was determined at diagnosis, and correlated to main clinical and biological features, as well as to the need of receiving any specific therapy during the course of the disease. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
(45 reference statements)
5
30
0
Order By: Relevance
“…36 Regulatory T cells are expanded in CLL, with numbers correlating with disease stage and prognosis, so it is probable that this T-cell subgroup regulates antitumor immune responses in CLL. [37][38][39] Since the first description of expanded populations of CMV specific T cells in CLL, it has been unclear as to the contribution of these populations to the T cell defects observed in this disease. 16,17 It has been suggested that these CMV specific T cells inhibit the function of other antigen-specific T-cell populations, either by a direct effect, or by constriction of the total T-cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…36 Regulatory T cells are expanded in CLL, with numbers correlating with disease stage and prognosis, so it is probable that this T-cell subgroup regulates antitumor immune responses in CLL. [37][38][39] Since the first description of expanded populations of CMV specific T cells in CLL, it has been unclear as to the contribution of these populations to the T cell defects observed in this disease. 16,17 It has been suggested that these CMV specific T cells inhibit the function of other antigen-specific T-cell populations, either by a direct effect, or by constriction of the total T-cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…An association between higher levels of circulating Th17 cell numbers and longer survival has been described (Jain et al 2012; Jadidi-Niaragh et al 2013; Sherry et al 2015). In addition to Th1/Th2/Th17 T cell subsets, increased frequency in T regs in CLL and MBL (Badoual et al 2009), and correlation with disease progression and time to first treatment has been shown in CLL patients (Beyer et al 2005; Giannopoulos et al 2008; Weiss et al 2011; Lad et al 2015; D’Arena et al 2011a, 2012). Finally, increased numbers of T FH cells have been consistently observed in CLL patients as compared to normal subjects although their association with clinical stage has been controversial (Ahearne et al 2013; Cha et al 2013).…”
Section: Cll As a Model System To Study Interactions Between Tumor Anmentioning
confidence: 99%
“…Interestingly, endogenous T cells may support the microenvironment responsible for the continued survival of CLL cells, as increased B cell proliferation in this disease appears to occur concomitant with the expansion of T lymphocytes 69,70 . This may also involve an increase in the absolute numbers of circulating regulatory T cells (T reg ), which are of negative prognostic significance in CLL 71-74 and could contribute to effector T cell dysfunction. In addition to increased T reg frequency, direct tumor-intrinsic mechanisms underlying poor T cell-mediated immunity may include suboptimal antigen presentation by CLL B cells 65,75 , the elaboration of immunosuppressive cytokines such as transforming growth factor (TGF)-β, Interleukin (IL)-6 and IL-10 76,77 , downregulation of costimulatory molecules 64,78 and down-modulation of CD40L on T cells 79 , as well as overexpression of the inhibitory CD200 receptor 80,81 .…”
Section: T Cells In Cllmentioning
confidence: 99%